TREATMENT OF Strongyloides stercoralis WITH IVERMECTIN AND THIABENDAZOLE - Huapaya, Pedro (2003)
OBJECTIVE: To describe the experience with ivermectin and thiabendazole in patients attended at the Tropical Medicine Institute “Daniel A. Carrión”- UNMSM. MATERIAL AND METHODS: During 2001 and 2002, ivermectin (0,2 mg/kg in single dosis) and thiabendazole (25 mg/kg/3days) were administered to 22 (Group 1) and 20 (Group 2) patients with diagnosis of Strongyloides stercoralis in stools. Controls were performed between 20 and 40 days following treatment. RESULTS: Mean age was 21,8 years (SD 22,6) for group 1 and 33,5 years (SD 14,2) for group 2. There were 12 males (54,5%) in group 1 and 7 (35%) in group 2. Ivermectin was 100% efficient while thiabendazole was 95%; only one case needed a second cycle because of high amount of parasites from the beginning; his next control was negative. Most frequent symptoms were diarrhea (71,4%), abdominal pain (61,9%) and epigastric pain (47,6%); all patients felt better after treatment. Only 2 cases (10%) from group 2 referred light nausea during the first day of treatment that disappeared at the second day. CONCLUSIONS: Both drugs ratify their efficacy and safety for Strongyloides stercoralis treatment making it necessary to have them in the national petitioner.